(untitled) - Brownell, Clarence Ludlow (London, 1904)
We lived so far from the travellers' track in Japan,-often where no foreigner had been before,-and had been and heard so much of what seemed to us humorous, tragic, quaint, or thought-worthy, that we dared to believe sometimes that we were getting glimpses of the real inner spirit of the native life- a spirit far different from that of the tourist-worn borders of this ancient and fascinating Land of the Rising Sun
Keywords: Japan,Nhật Bản; Description and travel,Mô tả và du lịch